Hidradenitis Suppurativa Is Characterized by Dysregulation of the Th17:Treg Cell Axis, Which Is Corrected by Anti-TNF Therapy - Moran, Barry; Sweeney, Cheryl M.; Hughes, Rosalind; Malara, Anna; Kirthi, Shivashini; Tobin, Anne-Marie; Kirby, Brian; Fletcher, Jean M. (Journal of investigative dermatology, 2017)
Hidradenitis suppurativa (HS) is a chronic, inflammatory, and debilitating disease of hair follicles with 1–4% prevalence and high morbidity. There is a dearth of information on the pathogenesis and immune dysregulation underlying HS; therefore, we carried out a detailed analysis of skin-infiltrating T cells. Cells isolated from skin biopsy samples and blood from HS patients and healthy control subjects were analyzed by 16-parameter flow cytometry to provide detailed profiles of CD4 T-cell subsets. We observed substantial infiltration of inflammatory T cells with a striking T helper (Th) type 17-skewed cytokine profile in HS skin; these cells expressed the Th17 lineage marker CD161 and IL-17, as well as proinflammatory cytokines GM-CSF, IL-22, IFN-γ, and tumor necrosis factor. Regulatory T cells were also enriched in HS lesional skin; however, the ratio of Th17 to regulatory T cells was nonetheless highly dysregulated in favor of Th17 cells. In contrast, lesional skin from anti-tumor necrosis factor–treated HS patients who showed substantial clinical improvement exhibited a significant reduction in the frequency of Th17 cells and normalization of the Th17 to regulatory T cell ratio. These data suggest that inhibition of pathogenic IL-17 via tumor necrosis factor blockade is associated with improvement in immune dysregulation in HS and may provide a rationale for targeting IL-17 in the disease.